Utilization of Ketapang Leaf Etil Asetic Fraction (Terminalia catappa) as A Bioreductor In Synthesis of Silver Nanoparticles and Analysis of The Antibacterial Properties - Nursyamsi Nursyamsi; Muhammad Zakir; Seniwati Dali (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2017)
Silver nanoparticles had been synthesis conducted in reduction method by using ethyl acetat fraction of catappa leaf (Terminalia catappa) as bioreductor. Silver nanoparticles was characterized by UV-Vis, FTIR and PSA measurement. The results showed that absorbance values increased with the increase of AgNO3 concentration. Maximum absorption of silver nanoparticles 1 mM dan 2 mM silver nanoparticles between 418-436,5 nm and 421-434 nm respectively. Functional groups that contribute in the synthesis was analyzed using Fourier Transform Infrared Spectroscopy (FTIR). Particle size was determined by using PSA. The result showed that 1 mM and 2 mM of silver nanoparticles were 53 nm dan 158 nm respectively. Antibacterial testing conducted by using agar diffusion method against Staphylococcus aureus, Basillus subtilis dan Escherichia coli activity inhibition diameter zone were 7,2 mm, 6,9 mm and 6,6 mm with incubation period was 48 hours.